Zoographie : Tiere in der zeitgenössischen Kunst. - Galerie Gmyrek, Düsseldorf (Düsseldorf : Galerie Gmyrek, 1985)
Anzinger, Siegfried ; Baselitz, Georg ; Beuys, Joseph ; Borges, Jorge Luis ; Brus, Johannes ; Chevalier, Peter ; Dahn, Walter ; Finkeldei, Bernd ; Hamm, Peter ; Höckelmann, Antonius ; Hödicke, K.H. ; Immendorff, Jörg ; Jocks, Heinz-Norbert ; Kamper, Dietmar ; etc.
Zoographie : Tiere in der zeitgenössischen Kunst, Galerie Gmyrek, Düsseldorf, 27.9. - 2.11.1985
boek